Legal Procedures For The Recovery Of The Proceeds Of Corruption Crimes In National And International Law (Journal of Namibian Studies : History Politics Culture, 2024)
This study aims to evaluate the effectiveness of the legal procedures followed in the process of recovering the proceeds of corruption crimes, which are considered among the most important legal mechanisms of national and international interest, so that they have become a major challenge for many public authorities, especially in light of the lack of full international cooperation to combat corruption on the one hand, and recourse to political considerations in some international practices on the other.